ELECTRONIC TOLL SYSTEM IN THE SLOVAK REPUBLIC AND RATIO OF BYPASSING VEHICLES - Poliak, Milos (Doprava a spoje, 2009)
This paper describes impacts of toll collection introduction on haulers. There is described current and prepare status of charges for use of roads in fist element of paper. Paper includes tables of current and prepare rate for using of roads and figures current and prepare tolling scope in Slovak republic. There is described impact of implementation of electronic toll on hauler in further element of paper.